Sticks and Stones may Break Your Bones, but Words can Break Your Spirit: Bullying in the Workplace - Vega, Gina; Comer, Debra R. (2005)
Workplace bullying has a well-established body of research internationally, but the United States has lagged behind the rest of the world in the identification and investigation of this phenomenon. This paper presents a managerial perspective on bullying in organizations. The lack of attention to the concept of workplace dignity in American organizational structures has supported and even encouraged both casual and more severe forms of harassment that our workplace laws do not currently cover. The demoralization victims suffer can create toxic working environments and impair organizational productivity. Some methods of protecting your organization from this blight of bullying are proposed. Bullying has always been part of the human condition; history is rife with references to abuse of power and unnecessary or excessive force. The classic bully story is of Joseph and his brothers, a tale of envy and hostility. The refinement of bullying to include various forms of legally defined social harassment is a relatively late phenomenon, however, dating to the Civil Rights Act of 1964. In the United States, bullying is not illegal, whereas it is illegal in many other countries. Bullying is not about benign teasing, nor does it include the off-color jokes, racial slurs, or unwelcome advances that are the hallmarks of legally defined harassment. Workplace bullying is the pattern of destructive and generally deliberate demeaning of co-workers or subordinates that reminds us of the activities of the schoolyard bully. Unlike the schoolyard bully, however, the workplace bully is an adult, usually (but not always) aware of the impact of his or her behavior on others. Bullying in the workplace, often tacitly accepted by the organizational leadership, can create an environment of psychological threat that diminishes corporate productivity and inhibits individual and group commitment. The two examples that follow will help to clarify the difference between harassment and bullying.
Keywords: workspace bullying